Constructing tourism market vulnerability indicator in Thailand - Soh, Ann Ni; Kuek, Tai Hock; Puah, Chin Hong (Springer Nature B.V., 2024)
This paper attempts to develop a tourism market vulnerability indicator for Thailand as a real-time monitoring instrument in mitigating vulnerability in Thailand’s tourism. The indicator is constructed by extracting a common vulnerability component using a dynamic approximate factor model with a blend of six variables of macroeconomics and tourism. This paper focused on the four dimensions of tourism market vulnerability that include physical, socio-cultural, economic, and institutional factors. Through the wavelet analysis, the empirical results shown in the wavelet coherence maps suggested that the constructed indicator leads tourist arrivals in Thailand and thus, can serve as an early signal monitoring instrument. Oil price shocks have also been studied since tourism is an energy-intensive sector. Analysis results from the wavelet coherence revealed a signifcant leading role of crude oil price in the Thailand tourism market. The results further validated the tourismled growth hypothesis and the economic-driven tourism growth hypothesis in Thailand. The empirical evidence shows that while higher visitor exports (LVE) positively correlate with international tourist arrivals (LTA), indicating a fourishing tourism sector, currency appreciation (LREER) negatively impacts arrivals due to increased travel costs. Additionally, infation (LCPI) also exhibits a negative relationship with LTA, suggesting that rising prices deter tourists. The sufcient evidence on the causal relationship between the examined series provide tourism practitioners and policymakers more information to formulate hedging strategies against tourism market vulnerabilities and future oil price movements for the policy planning of economic development in Thailand